Intraspecific taxonomy of plant genetic resources – Important for differentiation of medicinal and aromatic plants? - Lohwasser, Ulrike; Börner, Andreas; Marthe, Frank (Julius-Kühn-Archiv, 2016)
Taxonomy of plant genetic resources is an important input in characterising and evaluating cultivated plants and essential for identification and documentation of the diversity of genebank collections. In former times taxonomical determination was based only on morphological characters. Nowadays, new molecular and chemical methods and techniques are available for providing additional information. As examples, investigations of parsley (Petroselinum crispum [Mill.] Nyman, Apiaceae) and opium poppy (Papaver somniferum L., Papaveraceae) collections of the German genebank are demonstrated. In addition to morphological description, the molecular distance and the phylogenetic relationship of the accessions were performed with molecular marker analysis. Essential oil compound and content for parsley and the content of the five main alkaloids (morphine, codeine, thebaine, noscapine, papaverine) for opium poppy were measured with GC (gas chromatography) and HPLC (high pressure liquid chromatography), respectively. For parsley the results of the three methods support the existing taxonomy partly, a separation of root and leaf parsley was confirmed. However, the taxonomy of opium poppy should be revised because molecular and chemical data do not verify the morphological results. But nevertheless taxonomy of cultivated plants is an important tool to describe the variability of plant genetic resources.